2020
DOI: 10.1108/mf-08-2019-0396
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive market hypothesis and investor sentiments: global evidence

Abstract: PurposeThe purpose of this study is to investigate the adaptive market hypothesis (AMH) for 21 major global market indices for the period 1998–2018. These market indices cover the 16 largest global financial markets.Design/methodology/approachQuantile-regression methodology is employed to examine the market efficiency of a large number of financial markets from America, Europe and the Asia–Pacific region.FindingsThe results show that the returns in higher quantiles are negatively autocorrelated, and those in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…They concluded that Litecoin was the most efficient cryptocurrency, and Ripple was the least efficient one. Tripathi et al (2020) investigated the AMH for 21 major global market indices for 1998-2018. They employed quantile-regression methodology to scrutinize the market efficiency of 16 financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that Litecoin was the most efficient cryptocurrency, and Ripple was the least efficient one. Tripathi et al (2020) investigated the AMH for 21 major global market indices for 1998-2018. They employed quantile-regression methodology to scrutinize the market efficiency of 16 financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By applying the GARCH methodology, the AMH was specified as more useful than any other approach when explaining the evolving trend for the TOM effect. Tripathi et al (2020) applied quantile regression methodology to test the AMH in 21 major global market indices. Daily, weekly and monthly data were included in the analysis for the 1998-2018 period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, the findings support the AMH for the most well-established cryptocurrency market. Tripathi et al (2020) investigate the adaptive market hypothesis (AMH) for 21 major global market indices for 1998-2018. They employed quantile-regression methodology to scrutinize the market efficiency of 16 financial markets.…”
Section: Market Efficiency and The Adaptive Market Hypothesis (Amh)mentioning
confidence: 99%